2019
DOI: 10.1029/2018wr023864
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Fluctuations and Poroelasticity Can Generate Chaotic Advection in Natural Groundwater Systems

Abstract: Although steady, isotropic Darcy flows are inherently laminar and nonmixing in the absence of diffusion, it is well understood that transient forcing via engineered pumping schemes can induce rapid, chaotic mixing flows in groundwater. In this study we explore the propensity for such mixing to arise in natural groundwater systems subject to cyclical forcings, for example, tidal or seasonal influences. Using a conventional linear groundwater flow model subject to tidal forcing, we show that under certain condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
(85 reference statements)
1
21
0
Order By: Relevance
“…
In a recent paper (Trefry et al, 2019, https://doi.org/10.1029/2018wr023864), we showed that the interplay of aquifer heterogeneity and poroelasticity can produce complex transport in tidally forced aquifers, with significant implications for solute transport, mixing, and reaction. However, what was unknown was how broadly these transport dynamics can arise in natural groundwater systems and how these dynamics depend upon the aquifer properties and tidal and regional flow characteristics.
…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…
In a recent paper (Trefry et al, 2019, https://doi.org/10.1029/2018wr023864), we showed that the interplay of aquifer heterogeneity and poroelasticity can produce complex transport in tidally forced aquifers, with significant implications for solute transport, mixing, and reaction. However, what was unknown was how broadly these transport dynamics can arise in natural groundwater systems and how these dynamics depend upon the aquifer properties and tidal and regional flow characteristics.
…”
mentioning
confidence: 88%
“…In this paper we will study advective flow in the linear groundwater model over the tidal flow parameter space scriptQ𝒯×𝒢×𝒞, identify regions of anomalous transport and chaotic advection, and comment on how scriptQ and χ together control these topological transitions and the underlying physical mechanisms. Chaotic advection arises when fluid particles undergo chaotic orbits, leading to exponential stretching of fluid elements with time, rapid mixing, and augmented transport (Ottino, ; Trefry et al, ). Table summarizes the various dimensionless dynamical and heterogeneity parameters and provides a brief physical motivation for each.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the Darcy scale, anisotropic (Chiogna et al., 2015; Ye et al., 2015a, 2018) and heterogeneous flow fields (e.g., de Barros et al., 2012; Dentz et al., 2016) enhance plume dilution and reactive mixing. Variability in the hydraulic conductivity fields (Rolle et al., 2009; Werth et al., 2006; Ye et al., 2015c), topographic features (Bandopadhyay et al., 2018), and transient conditions (e.g., de Dreuzy et al., 2012; Kahler & Kabala, 2016; Piscopo et al., 2013; Sposito, 2006; Trefry et al., 2019) lead to spatially variable flow fields.…”
Section: Introductionmentioning
confidence: 99%
“…(1990) and Hopkins and McCarty (1995). Nevertheless, mixing can be enhanced by the heterogeneity and anisotropy of porous media (Bauer et al., 2009; Bennett et al., 2017; Castro‐Alcala et al., 2012; de Barros et al., 2015; Di Dato et al., 2016) and chaotic advection (e.g., Jones, 1991; Lester, Dentz, & Le Borgne, 2016, Lester, Trefry, & Metcalfe, 2016; Ottino, 1990; Trefry et al., 2019).…”
Section: Introductionmentioning
confidence: 99%